The Basics of public budgeting and financial management: a handbook for academics and practitioners - Menifield, Charles E. (United States of America: University Press of America, Inc., 2013)
This book is an introductory level budgeting and financial management textbook for students who are interested in learning how budgeting occurs in public and nonprofit organizations.
Chapter 1. The Context of Public Sector Budgets -- Chapter 2. Preparing a Budget Proposal -- Chapter 3. Personnel Services and Operating Budgets -- Chapter 4. Preparing a Capital Budget and a Capital Improvement Plan -- Chapter 5. Funding State and Local Budgets -- Chapter 6. Budgeting Techniques and Analytics Models -- Chapter 7. Financial Management -- Chapter 8. Effectively Communicating Data .
Includes bibliographical references.
Keywords: BUSINESS AND ECONOMICS; ACCOUNTING; FINANCE; GOVERNMENT AND BUSINESS